Personalizable Models For Business-To-Business Information Interchange In Communication Layers - Ting, Tin Tin (2011)
Business-to-Business standards have been proven in increasing the efficiency of the document interchange procedures by eliminating human interventions. However, the integration standards contain inherent inflexibilities in the communication layers. This thesis has attempted to review the existing standards by promoting and integrating possible personalizable modelling concepts into the standardized document interchange procedures. A conceptual framework for personalization modelling is the main research outcome. In particular, the push-pull models derivation and generation can be visualized by 3-circle Venn.